Midazolam oxidation in cattle liver microsomes: The role of cytochrome P450 3A. Issue 6 (7th September 2020) - Nassi, Alberto; Quintieri, Luigi; Merlanti, Roberta; Pezzato, Francesca; Capolongo, Francesca; Pauletto, Marianna; Dacasto, Mauro; Giantin, Mery
Abstract: In humans, the cytochrome P450 3A (CYP3A) subfamily is involved in midazolam (MDZ) biotransformation into 1′‐ and 4‐hydroxy metabolites, and the former serves as a probe for CYP3A catalytic activity. In veterinary species is still crucial to identify enzyme‐ and species‐specific CYP substrates; thus, the aim of this study was to characterize MDZ oxidation in cattle liver. A HPLC‐UV method was used to measure 1′‐ and 4‐hydroxy MDZ (1′‐ and 4‐OHMDZ, respectively) formation in cattle liver microsomes and assess the role of CYP3A by an immunoinhibition study. Moreover, MDZ hydroxylation was evaluated in 300 cattle liver samples and results were correlated with testosterone hydroxylation. Formation of both metabolites conformed to a single‐enzyme Michaelis–Menten kinetics. Values of Vmax and Km were 0.67 nmol/min/mg protein and 6.16 μM for 4‐OHMDZ, and 0.06 nmol/min/mg protein and 10.08 μM for 1′‐OHMDZ. An anti‐rat CYP3A1 polyclonal antibody inhibited up to 50% and 94% 1′‐ and 4‐OHMDZ formation, respectively. MDZ oxidation in liver microsomes was poorly correlated with testosterone hydroxylation. In conclusion, cattle metabolized MDZ to 1′‐OHMDZ and 4‐OHMDZ. The immunoinhibition results indicated a major contribution of CYP3As to 4‐OHMDZ formation and the involvement of other CYPs in 1′‐OHMDZ production, paving the way for further investigations.